Intensitas Serangan dan Parasitoid Larva Ulat Api (Setothosea asigna van Eecke) (Lepidoptera : Limacocidae) di Kebun Kelapa Sawit di PT X. Desa Ukui Kecamatan Ukui Kabupaten Pelalawan Provinsi Riau - Rustam, Rusli; Salbiah, Desita; Raimon, Raimon (Jurnal Agro Teknologi Tropika, 2016)
Parasitoids is one of natural enemies that have the potential to be developed and play a role in pests control Setothosea asigna van Eecke on oil palm plants in the field. The pests high attacks intensity S. asigna effect on the production of palm oil. The role of parasitoids in the field reduce the existence of pests S. asigna so that palm oil plant damage could be reduced. This study attempts to find out the attack intensity larva S. asigna and the form parasitoids associated with larva S. asigna. The study has carried out on PT. X Ukui Village, Ukui District, Pelalawan Regency, Riau Province and Laboratory of Plants Pest Faculty of Agriculture, University of Riau. This research is a survey with a method of purposive sampling on locations which the most be attacked by S. asigna with heavy attack criteria, consisting of 3 sample plants, location on each 10%, 9 plants so that obtained 27 sample plants. The research results show the number of attack intensity is 37%. The number S. asigna 4,59 each midrib. Parasitoids associated with larva S. asigna has not been found.